2012
DOI: 10.1002/jor.22134
|View full text |Cite
|
Sign up to set email alerts
|

Significance of circulating endothelial progenitor cells in patients with fracture healing process

Abstract: Fracture healing is a complex bone formation process, and neovascularization may contribute to new bone regeneration. The circulating endothelial progenitor cell (EPC) mobilization and homing could involve in neovascularization and vasculogenesis. In this study, we investigate the changes of circulating EPC during bone fracture healing, and the possible contribution of EPCs to increased neovascularization and fracture healing. The number of circulating EPCs was monitored in twenty-four patients with long bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Eghbali-Fatourechi et al noted that circulating osteoprogenitor cell numbers increased at least 4-fold in a patient who had sustained a severe fracture 20 days earlier [60]. Another study by Ma et al demonstrated that peripheral EPC numbers significantly increased in patients within 48 hours after fracture and peaked around 3 days after injury [61]. In light of these and similar studies we had expected to see increased numbers of circulating cells in fractured mice and that this response would be enhanced in the presence of AMD3100 mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Eghbali-Fatourechi et al noted that circulating osteoprogenitor cell numbers increased at least 4-fold in a patient who had sustained a severe fracture 20 days earlier [60]. Another study by Ma et al demonstrated that peripheral EPC numbers significantly increased in patients within 48 hours after fracture and peaked around 3 days after injury [61]. In light of these and similar studies we had expected to see increased numbers of circulating cells in fractured mice and that this response would be enhanced in the presence of AMD3100 mobilization.…”
Section: Discussionmentioning
confidence: 99%
“…Repair of the injured endothelium is accomplished in large part by recruitment of circulating endothelial progenitor cells (EPCs). The role of endothelial repair is being increasingly recognized as a potential therapeutic target to improve endothelial dysfunction, myocardial ischemic injury, kidney injury, and bone marrow microangiopathy (10,44,112,119). The endothelium of individuals who are obese and diabetic is prone to endothelial injury that can lead to endothelial dysfunction and microvascular and macrovascular complications.…”
Section: Cellular and Molecular Mechanisms Of Action Of Dpp-4i In Thementioning
confidence: 99%
“…Endothelial cells in forming callus vasculature can develop from a variety of sources, including, existing vessels of the periosteum and the intramedullary vasculature; circulating EPCs that are increased during fracture repair; or the bone marrow . Circulating EPCs are not only increased in rodent models, but are significantly increased in human patients at day three post‐fracture …”
Section: Fibrovascular Phase—endothelial and Mesenchymal Progenitors mentioning
confidence: 99%